Pengaruh Otonomi Keuangan, Akumulasi Surplus dan Sisa Lebih Perhitungan Anggaran (SiLPA) Terhadap Perubahan Belanja Modal - Afan Fernando; Vita Fitria Sari (Universitas Negeri Padang, 2022)
This study aims to determine the extent to which financial autonomy, surplus accumulation and excess budget calculations product can affect changes in the capital expenditure budget of district/city governments in Sumatra. The population in this study is the Regency/City in Sumatra in 2016-2019. This study uses secondary data. The sampling technique used purposive sampling technique with a sample of 51 districts/cities with a period of 4 years. Data analysis used panel data regression analysis. The results showed that financial autonomy, surplus accumulation had an effect on changes in capital expenditures. Meanwhile, the remainder of the calculation of the budget and gross regional domestic product has no effect on changes in capital expenditures.